2019
DOI: 10.1002/mnfr.201801265
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Pleurotus eryngii Ameliorated Dextran‐Sodium‐Sulfate‐Induced Colitis in Mice

Abstract: Scope Pleurotus eryngii, an edible mushroom, is widely consumed as a functional food for various health benefits due to its multiple bioactive components. There are growing interests in using whole‐food‐based strategies to prevent colonic inflammation via potential synergistic interactions among different components within the whole foods. However, limited research is focused on the inhibitory effects of the whole P. eryngii mushroom against inflammatory bowel disease (IBD). Methods and results The protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 34 publications
(39 reference statements)
2
37
0
Order By: Relevance
“…Although the pathogenesis of IBD is complex, accumulating evidence showed that the development of IBD is related to the imbalance of gut microbiota composition [ 28 ]. The present study indicate that DSS treatment caused the reduction of α diversity and the increase of relative abundance of pathogenic bacteria compared with the control group, which are consistent with the results of a previous study on human patients with colitis [ 29 , 30 , 31 ]. A recovery of α diversity and changes in fecal bacteria were observed after NaB administration.…”
Section: Discussionsupporting
confidence: 93%
“…Although the pathogenesis of IBD is complex, accumulating evidence showed that the development of IBD is related to the imbalance of gut microbiota composition [ 28 ]. The present study indicate that DSS treatment caused the reduction of α diversity and the increase of relative abundance of pathogenic bacteria compared with the control group, which are consistent with the results of a previous study on human patients with colitis [ 29 , 30 , 31 ]. A recovery of α diversity and changes in fecal bacteria were observed after NaB administration.…”
Section: Discussionsupporting
confidence: 93%
“…Compared to the NM group, the fecal concentrations of acetic acid, propionic acid, and butyric acid were significantly decreased by AOM/DSS treatment. The results were consistent with previous studies [34], and was supposed to be induced by the reduced abundance of SCFA-producing bacteria. The intake of millet significantly increased the contents of acetic acid, propionic acid and butyric acid relative to the AOM/DSS + rice group.…”
Section: Microbial Metabolites Of Foxtail Millet Activated Ahr and Gpcrssupporting
confidence: 93%
“…Probiotics such as Bifidobacterium breve can alleviate CRC by inhibiting the inflammatory reactions and DNA methylation of the host, thereby inducing colitis and polyp retrogression, and activating tumor suppressor gene expression. Furthermore, a decline in microbial diversity, which is a sign of microbial dysbiosis, is considered to be an important factor for the incidence of CRC [ 34 , 37 ]. In this study, the administration of AOM/DSS reduced the microbial diversity and abundance of several SCFA-producing bacteria, including norank_f_ Bacteroidales_S24-7 , Parabacteroides and Alloprevotella .…”
Section: Discussionmentioning
confidence: 99%
“…DSS can directly damage intestinal epithelial cells, destroy the integrity of the mucosal barrier, allow luminal bacteria to enter the lamina propria, and activate macrophages to secrete proinflammatory cytokines. The DSS model is therefore an important tool for deciphering the pathogenesis of colitis and assessing potential therapies (Chassaing, Jesse, Madhu, & Vijay-Kumar, 2014;Hu et al, 2019). The current aim of colitis therapy is to reduce recurrence and relieve symptoms (Pithadia & Jain, 2011).…”
Section: Introductionmentioning
confidence: 99%